2020
DOI: 10.1021/acsbiomaterials.9b01649
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Administration of Human Type III Collagen-Derived Biomaterial with High Cell-Adhesion Activity to Treat Vaginal Atrophy in Rats

Abstract: Vaginal atrophy (VA) is the thinning and drying of the vaginal walls, which can lead to a variety of symptoms. VA is usually initiated by decreasing estrogen levels in post-menopausal women; so, the traditional treatment of VA is hormone therapy (HT). Here, we sought nonhormonal therapies aimed at treating this condition safely and effectively. Collagen is an excellent biomaterial and has important biological functions in skin and mucosal tissues. In particular, collagen can bind to epithelial cells to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…This may contribute to the repair of the vaginal epithelium. [ 34 ] In addition, the results of TNF‐ α analysis showed that after 3 days of treatment, TNF‐ α secretion increased remarkably in the control group, which may trigger a downstream inflammatory response (Figure 6b). After 7 days of treatment, the CSNG and the antibiotic groups showed a recovery in TNF‐ α expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…This may contribute to the repair of the vaginal epithelium. [ 34 ] In addition, the results of TNF‐ α analysis showed that after 3 days of treatment, TNF‐ α secretion increased remarkably in the control group, which may trigger a downstream inflammatory response (Figure 6b). After 7 days of treatment, the CSNG and the antibiotic groups showed a recovery in TNF‐ α expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…Col III is generally co-exists with Col I in connective tissue and the proportion of Col III is typically greater during the wound healing and collagen development [ 13 ]. Recently, we investigated the interactions between a recombinant humanized type III collagen (rhCol III) and human fibroblasts via in vitro study to find a similar cell adhesion results as reported in the literature [ 14 , 15 ]. To further investigate the biological effect of rhCol III in vivo and provide evidence of validity to the commercialization, an animal model with damaged skin was successfully made via ultraviolet radiation, and rhCol III was implanted on schedule in an observation period of 8 weeks in this study.…”
Section: Introductionmentioning
confidence: 82%
“…Among natural polymers, such as chitosan, gelatin, silk and cellulose, collagen is a main composite in extracellular matrix and contributes as the most abundant protein in mammals [19a] . With its good biocompatibility, high cell affinity and low antigenicity, [19b] collagen has been widely used for biomedical applications, including guided bone regeneration, corneal reconstruction, [20] wound dressing, [21] therapeutic contact lenses, [22] etc. However, pure collagen membranes usually lack desirable mechanical properties, which may bring obstacles for clinical uses.…”
Section: Methodsmentioning
confidence: 99%